STRATEGY FOR HANDLING THE QUALITY OF CAUGHT SKIPJACK TUNA TRAWLER SHIP AT PPS KUTARAJA: STRATEGI PENANGANAN DAN MUTU IKAN CAKALANG HASIL TANGKAPAN KAPAL PUKAT LINGKAR DI PPS KUTARAJA - Putra, Demo Buana; Mustaruddin, Mustaruddin; Puspito, Gondo (Jurnal Teknologi Perikanan dan Kelautan, 2025)
One of the main commodities landed at the Oceanic Fishing Port (PPS) of Kutaraja is skipjack tuna (Katsuwonus pelamis), which has high economic value and strong export potential. However, the quality of skipjack tuna landed at PPS Kutaraja often declines due to poor post-harvest handling, such as uncontrolled storage temperatures and inadequate application of a proper cold chain. This study aims to formulate a quality control strategy model for skipjack tuna caught by purse seine vessels at PPS Kutaraja. The research employed descriptive methods and a SWOT analysis to identify internal and external factors systematically. Data were collected through interviews with 14 purse-seine captains and two experts familiar with the port’s conditions. Captains were selected using accidental sampling. The findings indicate significant opportunities to improve the quality of skipjack tuna landed at PPS Kutaraja. The proposed strategies include: (1) improving quality control from capture to fish auction sites (TPI), (2) providing training and education on good fish handling practices for fishers, (3) maintaining fish storage temperatures at 0°C until landing, (4) providing funding for the modernization of refrigerated fishing vessels, (5) facilitating certification for purse seine fishing and proper fish handling, (6) collaborating between port authorities and fishers to establish skipjack quality control standards at TPI, (7) enhancing human resources through certified fish handling training, and (8) cooperating between port authorities and vessel owners to design vessels equipped with freezer systems.